A thioacetamide interlayer anchoring TiO2 and (FAPbI3)1−x(MAPbBr3)x for high‐performance perovskite solar cells. Issue 10 (18th March 2021) - Wang, Jingjing; Chen, Yumin; Zhao, Andi; Guo, Minghuang; Zhu, Jingwei; Li, Yafeng; Wei, Mingdeng
Abstract: In the perovskite solar cells (PSCs), traps of the perovskite film or interface are the research focus, which can severely hinder charge transfer and benefit charge recombination, thus weakening the photoelectric performance of the devices. Herein, a Thioacetamide (TAA) interfacial layer is used to passivate the traps of PSCs. Comparing to the control device (17.65%), the TAA‐based solar cells can achieve an enhanced efficiency of 19.14%. It is found that the passivation caused by TAA occurs through the interactions of sulfur in TAA with undersaturated Pb in perovskite and Ti 4+ in TiO2, resulting in a faster and more efficient charge transfer and a greatly reduced trap density from 3.36 × 10 16  cm −3 to 1.93 × 10 16  cm −3 . It is shown that the modification method using TAA may be helpful for passivating traps and obtaining excellent photoelectric properties of PSCs.